Pueblos de indios del antiguo Obispado del Cusco - Viñuales, Graciela María (Pontificia Universidad Católica del Perú, 2015)
The former Bishopric of Cusco used to serve and encompass over 200 towns that now belong to the Departments of Cusco, Apurímac and part of Arequipa. They were the so called «pueblos de indios» («town of indigenous people») that had been formed during the colonial period. In order to delimit this portion of the land, this study focuses mainly on documents from the late 18th century. Three types of supplementary documents contributed to this research: numeric records, maps and descriptive texts. Some of these jurisdictions have changed, but we decided to maintain the division from the 1780’s, and use it to organize this study. The documentation gathered was not equally distributed; therefore, we had to resort to maps, current photographs and surveys, as well as anient photographs and engravings. Satellite images were used to get an idea of urban maps and determine details regarding the surroundings, access to and connections between towns. In a few cases, these images conﬁrmed that certain areas had been abandoned or had disappeared. This paper is a synthesis that involves the preexistence of indigenous communities and considers social, economic, architectural, artisanal, and religious issues. It also mentions important people such as Bishop Mollinedo, and proposes certain policies for heritage recovery.

El antiguo Obispado del Cusco atendía algo más de doscientas localidades que hoy pertenecen a los departamentos de Cusco y de Apurímac y parte de Arequipa. Se trata de los llamados «pueblos de indios» que se habían ido consolidando durante la época virreinal. Para deﬁnir esta porción del territorio la labor se basó principalmente en los documentos que se generaran a ﬁnales del siglo XVIII, cuando hubo tres actuaciones complementarias que ayudaron a organizar la investigación: registros numéricos, cartografía y textos descriptivos. Algunas de tales jurisdicciones se han alterado, pero se decidió mantener la división de la década de 1780 y basar en ella la organización del trabajo. La documentación obtenida fue dispar y necesitó apoyarse también en cartografía, levantamiento de planos y fotografía actuales, así como en grabados y fotos antiguas. Se usaron imágenes satelitales para obtener una aproximación a los planos urbanos y estimar detalles de entorno, accesos y nexos entre pueblos. En unos pocos casos esas imágenes conﬁrmaron abandonos y desapariciones. Este trabajo es una síntesis que involucra a preexistencias indígenas, mirando los temas sociales, económicos, arquitectónicos, artesanales y religiosos. Destaca a personalidades relevantes como el obispo Mollinedo y plantea algunas políticas de recuperación patrimonial.
Keywords: Cusco; Villages; Heritage; Colonial; Territory; Cusco; Pueblos; Patrimonio; Virreinato; Territorio; https://purl.org/pe-repo/ocde/ford#6.04.08